Neurofunctional correlates of glutamate and GABA imbalance in psychosis: a systematic review - Zahid, U; Onwordi, EC; Hedges, EP; Wall, MB; Modinos, G; Murray, RM; Egerton, A (Elsevier, 2022)
Glutamatergic and GABAergic dysfunction are implicated in the pathophysiology of schizophrenia. Previous work has shown relationships between glutamate, GABA, and brain activity in healthy volunteers. We conducted a systematic review to evaluate whether these relationships are disrupted in psychosis. Primary outcomes were the relationship between metabolite levels and fMRI BOLD response in psychosis relative to healthy volunteers. 17 case-control studies met inclusion criteria (594 patients and 538 healthy volunteers). Replicated findings included that in psychosis, positive associations between ACC glutamate levels and brain activity are reduced during resting state conditions and increased during cognitive control tasks, and negative relationships between GABA and local activation in the ACC are reduced. There was evidence that antipsychotic medication may alter the relationship between glutamate levels and brain activity. Emerging literature is providing insights into disrupted relationships between neurometabolites and brain activity in psychosis. Future studies determining a link to clinical variables may develop this approach for biomarker applications, including development or targeting novel therapeutics.